Treatment of Class II Division 1 Malocclusion using Cervical Headgear - Priska Lestari Hendrawan; Krisnawati Krisnawati (Faculty of Dentistry, Universitas Indonesia, 2013)
Class II division 1 malocclusions have many variation and treatment options. Choosing the right treatment begins with a correct diagnosis. The aim of this article is to describe treatment of Class II division 1 malocclusion in a growing patient using combined cervical headgear and non-extraction fixed orthodontic therapy. Class I molar and canine relationship was achieved with normal overbite and overjet. There is improvement in jaw relationship and facial profile. This correction was achieved by downward displacement and inhibition of the forward growth of maxilla with favorable growth of mandible, upper molar distalization and retraction of upper incisors from cervical headgear use. There was neither downward rotation of the mandible nor maxillary first molar extrusion. Treatment time, favorable mandibular growth pattern and patient compliance proved to be determining factors in the success of this treatment. DOI: 10.14693/jdi.v16i3.106